Transitions alimentaires en rural : pratiques et représentations habitantes - Perrine Vandenbroucke; Claire Delfosse (Bulletin de l’Association de Géographes Français)
While transition to sustainable food appears as an urban phenomenon, this article focuses on the practices and representations of the inhabitants of peri-urban and rural areas as eaters, residents and citizens. The article is based on a microsocial and qualitative approach conducted in four municipalities located on the Massif du Pilat and the territory of the Boucle du Rhône in Dauphiné. A survey conducted with 90 inhabitants revealed several specificities related to the rural and peri-urban context : a paradoxical relationship of geographical proximity to agriculture and farmers, greater logistical constraints for supply, and the transmission of know-how about meat. But the relationship of inhabitants to agriculture and food is impacted by global societal dynamics. This is reflected in the affirmation of a reflexivity around food, the reinvestment of practices and know-how around plants and the emerging social dynamics around food. Thus practices and representations of rural and periurban areas inhabitants is built on several socio-spatial scales, between anchorage and opening.